The use of medicine balls for speed & power development - Faccioni, A.
For the speed and power athlete, medicine balls can be used in the following ways. A large number of specific mid-torso exercises are done using a range of different sized medicine balls. General and specific body conditioning exercises (both isolations and multi-joint exercises) and sprint specific activities can also be performed.